Utilizing Ginger Root to Boost Immunity: A Case Study of Kedungkembar Village, Sidoarjo, Indonesia - Ambari, Yani; Rahmawati, Dewi; Meliana, Marthy; Ningsih, Arista Wahyu; Aristia, Bella Fevi; Klau, Irvan Charles Seran; Kusumaningrum, Yunita Dyah; Fitriyanti, Andira Aulia; Rohmah, Atina Wahdatar; Maghfiroh, Firda Intan (Journal of Community Practice and Social Welfare, 2024)
The body's immunity plays a crucial role in maintaining health and protecting against infections. One well-known method to enhance the immune system is by consuming herbal remedies, particularly ginger rhizomes. The components gingerol and curcumin found in ginger rhizomes function as antioxidants and anti-inflammatory agents, aiding in combating free radicals. Processing ginger rhizomes into herbal drinks is one form of utilization. The community in Kedungkembar Village hopes that training and processing herbal drinks from ginger rhizomes will help them understand the benefits of these herbal plants and how to process them into herbal drinks. This community service activity consists of three stages. The first stage involves field observations, the second stage includes counseling and lectures on the benefits of ginger and techniques for processing it into herbal drinks. The third stage is a demonstration of training in making herbal drinks from ginger rhizomes. This community service activity has been enthusiastically welcomed by the villagers. Its implementation proceeded smoothly and successfully enhanced the community's skills in processing ginger rhizomes into herbal drinks.